Ruminal bioavailability of minerals from King Grass (Pennisetum purpureum) fertilized with nitrogen - Avellaneda-Cevallos, Juan (2022)
The present research project was developed at the Pichilingue Tropical Experimental Station of the National Institute of Agricultural Research (INIAP) and at the Bromatological Analysis Laboratory of the UTE University. The effect of nitrogen fertilization with urea (0, 25, 50 and 75 kg of N ha-1) on in situ ruminal degradability (bioavailability) of the macrominerals (Ca, P and Mg) was evaluated) of the King Grass harvested at 40 days of regrowth. A randomized complete block design was used for the statistical analysis, where the blocking criteria was the animal where the ruminal incubation was performed, respectively. Nitrogen fertilization levels caused changes in ruminal bioavailability (degradation) of Ca, P and Mg of Pennisetum purpureum grass at different incubation hours, an action that in most cases affected the degradation kinetics of the grass in their different fractions (soluble fraction (A), insoluble but potentially degradable fraction (B), unpleasant fraction (c). Potential for ruminal degradation (A+B).